2008
DOI: 10.1097/prs.0b013e31818459b4
|View full text |Cite
|
Sign up to set email alerts
|

Shoulder Function after Harvesting a Thoracodorsal Artery Perforator Flap

Abstract: Donor-site morbidity after harvesting a thoracodorsal artery perforator flap was reduced to a minimum. Therefore, perforator flaps should be considered in reconstruction whenever adequate perforators can be identified and safely dissected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 15 publications
3
49
0
Order By: Relevance
“…Previous reports, using retrospective and smaller designs, have already suggested that the latissimus dorsi flap is safe with regard to the functional aspects of arm mobility. [10][11][12]22 However, our study is the first prospective confirmation of these trends. To our knowledge, this is the first study to compare the mobility of the same arm presurgically and postsurgically, together with the prevalence of postsurgical complications, in women who had or had not undergone the latissimus dorsi flap procedure.…”
Section: Discussionsupporting
confidence: 36%
See 1 more Smart Citation
“…Previous reports, using retrospective and smaller designs, have already suggested that the latissimus dorsi flap is safe with regard to the functional aspects of arm mobility. [10][11][12]22 However, our study is the first prospective confirmation of these trends. To our knowledge, this is the first study to compare the mobility of the same arm presurgically and postsurgically, together with the prevalence of postsurgical complications, in women who had or had not undergone the latissimus dorsi flap procedure.…”
Section: Discussionsupporting
confidence: 36%
“…In general, studies are based on small sample sizes, and none has compared women who underwent reconstruction with controls who did not (comparisons are instead made with the contralateral arm). [10][11][12] In a recent report, we preliminarily assessed the impact of the latissimus dorsi flap procedure Immediate Breast Reconstruction with a Latissimus Dorsi Flap Has No Detrimental Effects on Shoulder Motion or Postsurgical Complications up to 1 Year after Surgery on women who underwent immediate breast reconstruction compared with their counterparts who were treated with mastectomy alone. 13 Although the reduction of shoulder motion was severe on immediate postsurgical assessment, there was no detectable latissimus dorsi flaprelated restriction of shoulder range of motion up to 4 weeks postoperatively.…”
mentioning
confidence: 99%
“…The dorsal silhouette is preserved, as the thickness of the latissimus dorsi muscle is not modified by flap harvesting. Preservation of the motor nerve of latissimus dorsi ensures maintenance of muscle strength after surgery as well as a full range of shoulder movements [18]. The site of the scar is particularly appreciated by female patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, the shoulder functions were evaluated by measuring the LD muscle strength and thickness after harvesting the pedicled thoracodorsal artery perforator (TDAP) flap in patients who underwent breast surgery, and similar outcomes were obtained between the operated and unoperated sides. 11 Under the name of ''muscle sparing LD flap,'' some pedicled flaps were recently used for partial 12 and total breast reconstruction 8,9 in mastectomy patients, as well as trunk and upper extremity reconstruction, 13 by taking lateral strip of the LD muscle with the flap, which contains the descending branch of the thoracodorsal artery and its perforators. The pivot point of these pedicled flaps was at the bifurcation of the main pedicle into the descending and transverse branches, and the transverse vessel along with the main thoracodorsal nerve was left in situ.…”
Section: Discussionmentioning
confidence: 99%